Cultural Entrepreneurship in Cinema in the Discourse of Film Producers in the Brazilian State of Pernambuco - Guerra, José Roberto Ferreira; Paiva Júnior, Fernando Gomes; Berenguer, Chris (Organizações & Sociedade, 2025)
Cultural entrepreneurship is a phenomenon that manifests itself in the cultural peculiarities of the activities of producers that have an impact on the creation of symbolic artifacts of an artistic nature with repercussions that go beyond those of the kind of production envisioned by the classical model of entrepreneurship. The current study aims to comprehend the dynamics of cultural entrepreneurship in the Pernambuco film production environment in accordance with the circuit of culture. It was conducted semi-structured interviews with Pernambuco audiovisual producers and created an explanation framework based on the circuit of culture. The corpus comprises a series of interviews with six local filmmakers, analyzed using French discourse analysis. Symbolic artifacts are configured by the representation of emerging identities related to hubs that lie outside of the mainstream of mass-media production in Brazil. Filmmaking in Pernambuco involves cultural entrepreneurship, and it is indicative of the importance of the film production output of this region. The generation of social capital by cultural entrepreneurship is bolstered by human capital and opposition to the prevailing economistic bias according to which the role of a cultural producer is confined to the actual making of films.